An educational tool design for the course of signal processing based on Matlab GUI - Han Ping; He Weikun; Shi Qingyan; Han Yan (2014 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE), 2014)
This paper presents an interactive and visual educational tool developed for teaching and learning in the course of signals and systems, digital signal processing. It is built with five main function modules, which are signal collecting, signal analysis, linear system analysis, filter design and signal processing techniques application module. Matlab GUI is used to design the tool. Feedback from students shows that teaching and learning with this tool, they can understand knowledge points of the courses much easier and their learning interest is stimulated obviously. That means an appropriate teaching tool can conduct a positive impact on students.